A walk in the sun - Brown, Harry, 1917-1986.; Milestone, Lewis, 1895-1980; Rossen, Robert, 1908-1966; Andrews, Dana, 1909-1992; Lewis Milestone Productions; Cinetel Films ([Los Angeles, CA] : Lewis Milestone Productions, 1945)
Depicts the horrors of war as seen through the eyes of a platoon of young American infantrymen. A renactment of the famed Texas Division's surprise attack on the Germans at Salerno.
Originally released as a motion picture in 1945.
Based on: A walk in the sun / by Harry Brown.
Released through Twentieth Century Fox Film Corporation.
Dana Andrews, Richard Conte, George Tyne, John Ireland, Lloyd Bridges, Sterling Holloway, Norman Lloyd, Herbert Rudley, Richard Benedict.
Cinematographer, Russell Harlan; editor, Duncan Mansfield; music, Earl Robinson; musical score, Fredic Efrem Rich.
In English.
Keywords: World War, 1939-1945 -- Campaigns -- Italy -- Drama; Salerno, Battle of, Salerno, Italy, 1943 -- Drama; War films; Feature films; Internet videos; Streaming video